2005
DOI: 10.1159/000086445
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mixed Bullous Disease of Epidermolysis bullosa acquisita and Linear IgA Bullous Dermatosis

Abstract: A 75-year-old Japanese male visited us with bullous eruptions on the extremities. Physical examination revealed large bullae on the hands, lower legs and feet. The oral mucosa was also involved. Histology disclosed subepidermal blister with inflammatory cell infiltrates in the dermis. Direct immunofluorescence showed deposits of IgG and IgA at the cutaneous basement membrane zone. Indirect immunofluorescence on 1 M NaCl-split human skin sections demonstrated that the patient’s IgG antibodies reacted with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…No known dermal antigens, e.g. C7, which could explain the symmetrical mirror labelling below the LD, were also targeted by the circulating autoantibodies as previously reported . One explanation might be that LAD‐1 and LABD97, which are soluble polypeptides generated by proteolytic cleavage of the BP180 ectodomain within its NC16A domain, secondarily partially migrated to the DEJ dermal side.…”
Section: Discussionmentioning
confidence: 71%
“…No known dermal antigens, e.g. C7, which could explain the symmetrical mirror labelling below the LD, were also targeted by the circulating autoantibodies as previously reported . One explanation might be that LAD‐1 and LABD97, which are soluble polypeptides generated by proteolytic cleavage of the BP180 ectodomain within its NC16A domain, secondarily partially migrated to the DEJ dermal side.…”
Section: Discussionmentioning
confidence: 71%
“…Cases reported to show IgA autoantibodies to the 290-kDa C7 may be diagnosed as sublamina densa-type LABD or IgA-mediated AEB. However, other clinical characteristics, such as milia and atrophic scarring, can be used to differentiate AEB from LABD [208]. LABD with predominant mucosal involvement can mimic CP clinically, but differentiates by immunofluorescence findings from other bullous diseases.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…A Japanese review of 213 patients with LABD found both IgA and IgG anti-BMZ antibodies in approximately 20% of the cases [216]. Therefore, several authors consider them to be overlap syndromes and prefer the designation of linear IgA/IgG bullous dermatosis (LAGBD) [120,194,208]. LAGBD comprises a heterogeneous group of diseases, and most cases show pruritic vesiculobullous eruptions similar to those of LABD [212].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Although coexistence of autoantibodies belonging to different autoimmune blistering diseases [16, 17], and clinical overlaps of BP and EBA [18, 19], have been described previously, our case is the first describing a patient who first had BP that relapsed as EBA. The physiopathology of both overlap and transition remains unclear.…”
Section: Discussionmentioning
confidence: 71%